Respuesta :
Answer:
If X is the starting weight, total pounds lost in three months is
(0.132X + 2.37)lbs
Step-by-step explanation:
Let the starting weight be X(lb)
Let the target ending weight be Y(lb)
Since Rollie ended with 3(lbs) above goal weight, final weight is Y+3(lb)
Each month, Rollie lost 1/3 of the difference between current weight and goal weight, hence
In the first month, Rollie lost 1/3 of (X - Y)
but since Rollie ended up with 3lbs above target ending weight, the actual weight loss is 1/3(X - Y) + 3
Hence by the end of the first month, Rollie's new weight is X - (1/3(X - Y)) + 3
which is equal to
X - 1/3X + 1/3Y - 3.
= 2/3X + 1/3Y - 3
By the second month, Rollie's starting weight is 2/3X + 1/3Y - 3(lb)
while her target ending weight still remains (Y)
but the actual ending weight is Y + 3
hence in the second month, Rollie lost 1/3(2/3X + 1/3Y - 3 - Y) + 3
= 2/9X + 1/9Y - 1 - 1/3Y + 3
= 2/9X - 2/9Y + 2
hence by the end of the second month, Rollie's new weight is
(2/3X + 1/3Y - 3) - (2/9X - 2/9Y + 2)
= 2/3X - 2/9X + 1/3Y + 2/9Y - 3 - 2
= 4/9X + 5/9Y - 5
By the third month, Rollie's starting weight is 4/9X + 5/9Y - 5(lb)
while her target ending weight still remains (Y)
but the actual ending weight is Y + 3
hence in the third month, Rollie lost 1/3(4/9X + 5/9Y - 5 - Y) + 3
= 4/27X + 5/27Y - 5/3 - 1/3Y + 3
= 4/27X - 4/27Y + 4/3 ------------------------- eqn (*)
hence by the end of the third month, Rollie's new weight is
(4/9X + 5/9Y - 5) - (4/27X - 4/27Y + 4/3)
= 4/9X - 4/27X + 5/9Y + 4/27Y - 5 - 4/3
= 8/27X - 19/27Y - 19/3
Hence in three months, Rollie's new weight is 8/27X - 19/27Y - 19/3
To ascertain how much weight Rollie lost in three months, there is need to equate the estimated ending weight to the final weight (Y + 3)
Therefore:
8/27X - 19/27Y - 19/3 = Y + 3
this implies that
8/27X - 19/27Y - Y - 19/3 - 3 = 0
8/27X - 36/27Y -28/3 = 0
Since Y is the target ending weight
the ending weight is generated by solving the equation with respect to Y
36/27Y = 8/27X - 28/3
multiply through by 27/36
Y = 2/9X - 7
Hence weight lost in three months is generated by substituting for Y = 2/9X - 7 in eqn (*)
Since eqn * is 4/27X - 4/27Y + 4/3
the lbs lost in three months is
4/27X - 4/27(2/9X - 7 ) + 4/3
= 4/27X - 8/243X + 28/27 + 4/3
= (32/243)X + 64/27
which in decimal is
(0.132X + 2.37)lbs
The total pounds of weight that will be lost in three months will be (0.132x + 2.37)lbs.
How to compute the weight?
The starting weight is illustrated by x. The target ending weight is illustrated by y.
In the first month, the weight list by Rollie will be 1/3 × (x - y) and her new weight will be:
= 2/3x + 1/3y - 3
In the second month, the starting weight will be 2/3x + 1/3y - 3. The weight lost by the end of the second month will be:
= 1/3 × (2/3x + 1/3y - 3) + 3
= 2/9x - 2/9y + 2
The new weight will be:
= (2/3x + 1/3y - 3) - (2/9x - 2/9y + 2)
= 4/9x + 5/9y - 5
In conclusion, the weight lost in three months will be:
= 4/27x - 4/27(2/9x - 7) + 4/3
= 4/27x - 8/243x + 28/27 + 4/3
= 32/343x + 64/27
= 0.132x + 2.37
In conclusion, the total pounds of weight that will be lost in three months will be (0.132x + 2.37)lbs.
Learn more about weight on:
https://brainly.com/question/86444